Estimation of regression factors for extending part lactation milk yield records of Red Chittagong Cattle (RCC) in Bangladesh - Md. Ruhul Amin; Md. Ahsan Habib (2012)
Regression factors for extending part lactation milk yield from test-day records were estimated from the within herd analysis of age at calving and season of calving corrected monthly 854 test-day records from 117 lactations of 43 Red Chittagong Cows (RCC) at Bangladesh Agricultural University, Mymensingh, Bangladesh taking data from 2005 to 2011. The best single month for predicting total milk yields by regression method is 5th month’s test day record with correlation coefficient of 0.81 with complete yield. On the other hand the poorest month for predicting total milk yield is 8th month’s record due to lowest correlation coefficient of 0.70 with complete yield. In case of cumulative monthly records, the more month’s records will be included the more accuracy of prediction will be obtained as indicating the progressive correlation coefficients between cumulative monthly yield and complete yield for each added month’s records. The development of regression factors for RCC in this study is first time in Bangladesh for only one herd including very small sample size. However, further study with more herds included more samples need to be considered for reliable estimation of regression factors for the genetic evaluation of RCC cattle.